Case-mix & patients' reports of outcome in Independent Sector Treatment Centres: Comparison with NHS providers - van der Meulen Jan; Lewsey Jim; Jamieson Liz; Browne John; Copley Lynn; Black Nick (BMC, 2008)
Abstract Background There has been considerable concern expressed about the outcomes achieved in Independent Sector Treatment Centres (ISTCs) introduced in England since 2003. Our aim was to compare the case-mix and patients' reported outcomes of surgery in ISTCs and in NHS providers. Methods Prospective cohort study of 769 patients treated in six ISTCs and 1895 treated in 20 NHS providers (acute hospitals and treatment centres) in England during 2006-07. Participants underwent one of three day surgery procedures (inguinal hernia repair, varicose vein surgery, cataract extraction) or hip or knee replacement. Change in patient-reported health status and health related quality of life (measured using a disease-specific and a generic (EQ-5D) instrument) was assessed either 3-months (day surgery) or 6-months (hip/knee) after surgery. In addition patient-reported post-operative complications and an overall assessment of success of surgery were collected. Outcome measures were adjusted (using multivariable regression) for patient characteristics (disease severity, duration of symptoms, age, sex, socioeconomic status, general health, previous similar surgery, comorbidity). Results Post-operative response rates varied by procedure (73%-88%) and were similar for those treated in ISTCs and NHS facilities. Patients treated in ISTCs were healthier, were less likely to have any comorbidity and, for those undergoing cataract surgery or joint replacement, their primary condition was less severe. Those undergoing hernia repair or joint replacement were less likely to have had similar surgery before. When adjustment was made for pre-operative characteristics, patients undergoing cataract surgery or hip replacement in ISTCs achieved a slightly greater improvement in functional status and quality of life than those treated in NHS facilities, while the opposite was true of patients undergoing hernia repair. No significant differences were found for the two other procedures. Patients treated in ISTCs were less likely to report post-operative problems than those treated in NHS facilities for cataract surgery (Adjusted Odds Ratio 0.35; 95% CI 0.17-0.70), hernia repair (0.42; 0.28-0.63) and knee replacement (0.44; 0.28-0.69). Most patients described the result of their operation as excellent, very good or good, regardless of where they were treated. Conclusion The case-mix of patients treated in ISTCs differs from that in NHS providers, in line with the intention of the contracts. Caution is needed in interpreting the observation that patients treated in ISTCs reported slightly better outcomes as very few ISTCs participated, case-mix adjustment might have been insufficient, and patients' reports might have been biased as they were more likely to be satisfied with the way they were treated.